P-015 Long-term economic impact of the first pass effect (FPE) in the treatment of stroke with the EMBOTRAP II device (in ARISE-II). (22nd July 2019) - Zaidat, O; Saver, J; Mattle, H; Ribo, M; Narata, A; Yoo, A; Bozorgchami, H; Crivera, C; Cameron, H; Andersson, T
Abstract : Introduction: The first pass effect (FPE) is the ability to restore near or complete revascularization (modified Thrombolysis in Cerebral Ischemia [mTICI] ≥2c) of acutely blocked cerebral arteries in a single thrombectomy device pass. FPE has been shown to be an independent predictor of good functional outcomes (modified Rankin Scale [mRS] ≤2), a goal of stroke therapy that impacts healthcare costs, and is associated with reduced 90-day mortality and fewer adverse events. A separate analysis of ARISE-II data showed that the FPE was associated with reduced procedural and in-patient healthcare resource use (length of stay, days in the intensive care unit, standard bed days, and devices used) and accompanying short-term costs; however, the long-term economic impact of achieving the FPE has not been assessed. Methodology: Data were obtained from a single-arm, prospective, multicenter study assessing the EMBOTRAP II device, ARISE-II (n=227). Patients who did not achieve complete revascularization were excluded. Among those who achieved complete revascularization (mTICI≥2c), the proportion of patients achieving each mRS score was assessed, stratified by the FPE status. Long-term costs per mRS score, obtained from a 2015 U.S. cost-effectiveness analysis that projected annual post-hospitalization inpatient/outpatient and nursing home costs using data from the National Death Index and Centers for Medicare and Medicaid Services (CMS), were applied to all patients. Post-hospitalization costs, in 2018 USD, were then compared between patients that did or did not achieve the FPE and incremental differences were calculated for a 1-year time horizon. Results: In ARISE-II, 76% of patients (n=172) achieved complete revascularization; among these patients, 53% achieved the FPE. A significantly higher percentage of patients that achieved the FPE had good functional outcomes vs. those that did not achieve the FPE (80.5% vs. 61.0%, p=0.006). Estimated annual post-hospitalization costs were lower among patients that achieved FPE vs. those that did not achieve FPE, leading to estimated per-patient cost-savings of $3, 876 (table 1). In the absence of cost data reported in ARISE-II, costs for healthcare resource use were obtained from the literature, which may not be generalizable across settings and is a limitation of this analysis. Additionally, the cost-effectiveness analysis used to inform the long-term costs per mRS score did not report costs for death (i.e., mRS 6), which had a lower incidence among patients who achieved the FPE vs. those who did not achieve the FPE (5.75% vs. 14.29%). Conclusion: Among patients with final complete reperfusion (mTICI≥2c), achieving FPE may lead to long-term per-patient cost-savings of $3, 876 in the first year due to improved functional outcomes. Disclosures: O. Zaidat: 1; C; Cerenovus, Stryker, Medtronic, Penumbra, Genentech, Tesla Clinical Trial. 2; C; Cerenovus, Stryker, Medtronic, Penumbra. J. Saver: 2; C; Cerenovus, Stryker, Medtronic, Rapid Medical. H. Mattle: 1; C; Neuravi/Cerenovus. 2; C; Neuravi/Cerenovus. 3; C; Neuravi/Cerenovus. M. Ribo: 1; C; Stryker, Medtronic. 2; C; Cerenovus, Stryker, Medtronic, Anaconda Biomed. 4; C; Anaconda Biomed. A. Narata: None. A. Yoo: 1; C; Cerenovus, Stryker, Medtronic, Penumbra, Genentech. 2; C; Cerenovus, Genentech, Zoll Circulation. 4; C; Insera Therapeutics. H. Bozorgchami: 2; C; Cerenovus, Stryker, Coherex. C. Crivera: 4; C; Johnson & Johnson. 5; C; Johnson & Johnson. H. Cameron: 2; C; Employee of Cornerstone Research Group, contracted by Cerenovus. T. Andersson: 2; C; Cerenovus, Anaconda, Medtronic, Ablynx, Amnis Therapeutics, Rapid Medical.